Razvoj zakonskega urejanja lobiranja v Sloveniji kot dopolnitev demokracije - Igličar, Albin (Podjetje in delo, 2014)
Back in 1990s the first lobbying organisations emerged in Slovenia. In 1994 a lobbyist section was founded within the Public Relations Society of Slovenia, which also adopted a lobbyist code of conduct that same year. The Parliament was to respond to the emergence of lobbying by initiating the formation of a group of experts, which prepared a draft law on the basis of a comparative study of legislation in states with an established lobbying culture and tradition. In 1998 group of MPs submitted a draft of the lobbying act to the legislative procedure, but it wasn't adopted. Slovenia went from the first attempts at statutory regulating lobbying to developing a certain level of culture in the field of lobbying. On this foundation, the Integrity and Prevention of Corruption Act of 2010 established a legal framework for lobbying.
Keywords: democracy; demokracija; lobiranje; odnosi z javnostmi; pravna ureditev; Slovenia; Slovenija